Legalitas Lingkungan Hidup dalam Perspektif Keadilan dan Hukum Administrasi Negara - Handoyo, Budi (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
The law does not only regulate human interests alone, but also both individuals and society. Moreover, the law is also required to manage the interests of the environment in which humans live in order to achieve a harmonious balance. Law aims to realize, fairness, expediency and legal certainty. Damage to the environment as we see now is not separated from the mistakes of mankind's view of nature. During this time, humans have colonized by ethics anthropocentric perceive and put themselves in the context of the universe. Anthropocentric understand, very detrimental environmental sustainability as opposed to the concept of justice. Justice can be meaningful if the legality, a legislation was fair if the rule really is applied. Legality is called the rule of law serves to ensure the protection of the welfare of environmental justice. It is characterized by the issuance of Law No. 32 of 2009 on the Protection and Environmental Management. This Act utilizing various legal stipulations, administrative law, civil law, and criminal law.